2013
DOI: 10.3389/fimmu.2013.00352
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic Heart Disease: Molecules Involved in Valve Tissue Inflammation Leading to the Autoimmune Process and Anti-S. pyogenes Vaccine

Abstract: The major events leading to both rheumatic fever (RF) and rheumatic heart disease (RHD) are reviewed. Several genes are involved in the development of RF and RHD. The inflammatory process that results from S. pyogenes infection involves the activation of several molecules such as VCAM and ICAM, which play a role in the migration of leukocytes to the heart, particularly to the valves. Specific chemokines, such as CXCL3/MIP1α as well as CCL1/I-309 and CXCL9/Mig, attract T cells to the myocardium and valves, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 41 publications
0
66
0
1
Order By: Relevance
“…Second, platelets play other roles in several fields in addition to prevention of bleeding, such as inflammation and immune responses 22. RHD is an autoimmune disease, and inflammatory response would be ongoing, even in its chronic phase 23, 24. Persistent inflammation might cause excessive consumption of platelets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, platelets play other roles in several fields in addition to prevention of bleeding, such as inflammation and immune responses 22. RHD is an autoimmune disease, and inflammatory response would be ongoing, even in its chronic phase 23, 24. Persistent inflammation might cause excessive consumption of platelets.…”
Section: Discussionmentioning
confidence: 99%
“…22 RHD is an autoimmune disease, and inflammatory response would be ongoing, even in its chronic phase. 23,24 Persistent inflammation might cause excessive consumption of platelets. Third, RHD is known to be induced by complex immune events.…”
Section: Discussionmentioning
confidence: 99%
“…Ccr7 and Cxcl9 clustered under Factor 3 (Table 2). Cxcl9 is an antimicrobial gene that encodes a protein involved in T-cell attraction; the encoded protein binds to C-X-C motif chemokine 3 and is a chemo-attractant for lymphocytes, a general function of C-X-C chemokines (Le et al, 2004); this potentially explains the moderate involvement of Cxcl9 with Cxcl1 gene of the same family from Factor 1 ( Table 2) (Guilherme and Kalil, 2013;Yang et al, 2004). A study by Syed et al showed that Ccr7 was downregulated in asthma (an inflammatory disorder), and played an important role in the migration of lymphocytes (Syed et al, 1999).…”
Section: Trends In Genes Expressionmentioning
confidence: 97%
“…(17, 18)]. GAS M proteins have been studies extensively and it is one of the important GAS proteins involved in inducing the autoimmune process.…”
Section: Current Concepts Of Pathogenesis Of Rheumatic Heart Diseasementioning
confidence: 99%